MODEL BIMBINGAN KESALEHAN SOSIAL TERHADAP MORAL AWARENESS - Ilham Hamid (Jurusan Bimbingan dan Penyuluhan Islam, 2022)
The main problem of this study is (1) What is the form of a social piety guidance model that can increase the moral awareness of students of SMK Negeri 3 Sinjai? (2) How is the validity and practicality of social piety guidance to increase moral awareness of students of SMK Negeri 3 Sinjai? (3) Is the application of the social piety guidance model effective in increasing the moral awareness of students of SMK Negeri 3 Sinjai? This study aims (1) To find out the form of a social piety guidance model that can increase moral awareness of students of SMK Negeri 3 Sinjai, and (2) To find out the validity and practicality of social piety guidance for moral awareness of students of SMK Negeri 3 Sinjai, and (3) To find out the application of the social piety guidance model effective in increasing moral awareness of students of SMK Negeri 3 Sinjai. The design of this research is R&D (research and development). The research phase includes (1) initial research and information collection, (2) development planning, (3) initial product development, (4) concepts, (5) initial field tests (expert validation), (6) preliminary revisions, (7) small group tests. The data collection technique used is to use questionnaires, observations, and interviews. The results of this study (1) The social piety guidance model produced is in the form of a guide or module that contains the background, goals, objectives, systematics of activities and time allocation, scenarios of group guidance activities, application of group guidance activities in the online form, stage of group guidance activities, place of activity, the competence of counselors and the content of guide materials, (2) The student's moral awareness social piety guidance model and its guidelines are considered valid and practical to improve students' moral reasoning at SMK Negeri 3 Sinjai, (3) The social piety guidance model for the moral awareness of students of SMK Negeri 3 Sinjai is effective in improving students' moral reasoning.